PERANCANGAN GAME AYO BERSIH UNTUK ANAK MENGGUNAKAN METODE SYSTEM DEVELOPMENT LIFE CYCLE WATERFALL - Muhajir Lubis (Politeknik Bisnis Indonesia, 2022)
One of the popular pastimes among young people today is video games, which are educational and for entertainment purposes only. Video games usually only focus on story and game mechanics. Gaming is currently an alternative entertainment for various groups. In this research we aim to make game software in the form of RPG games using RPG Maker MV software. The purpose of this research is to design an educational game Ayo Clean for children so that children practice maintaining cleanliness or a clean lifestyle every day. The research method used to make this RPG game is the System Development Life Cycle (SDLC) waterfall, where the research stage is in the form of the final stage, returning to the initial stage which forms a cycle or life cycle. Based on the results of research on educational animations to keep the environment clean for children 7-9 years old, it can be concluded that this method can make it easier for children to maintain cleanliness. However, 3. This game is already under development. Based on the results of the questionnaire, there is a section on how interesting the game is that 45 respondents chose not interesting, therefore the authors developed the game. The educational game Ayo Bersih using the System Development Life Cycle method (children 7-9 years old) using RPG Maker MV can be implemented properly.